Truth in a pill - Samajdar, Shambo S.; Venkatraman, Shravan; Joshi, Shashank; Biswas, Kaushik; Saboo, Bharat (International Journal of Basic & Clinical Pharmacology, 2024)
In 1937, the elixir sulphanilamide disaster was one of the mass poisonings. It occurs due to the presence of the diluent diethylene glycol in the elixir preparation of sulphanilamide. Because of its therapeutic use, around 100 patients died. In response to the calamity, Federal Food, Drug and Cosmetic Act was passed in the year 1938 by U.S congress and this ensured the proof of safety before the drug comes to market. The similar incident occurred for thalidomide in late 1950s and early 1960s when the drug was used for the treatment of nausea in pregnant women and resulted in children with birth defects. The development of drugs is a complex and costly process and it takes around 10-15 years for the drug to develop. Because of these reasons, the development of generic drugs is essential and this review will deal about the use of generic drugs and also its advantages with limitations.